Radionuclide Therapy of HER2-Expressing Xenografts Using [177Lu]Lu-ABY-027 Affibody Molecule Alone and in Combination with Trastuzumab; Cancers; Vol. 15 - iss. 9 - Liu Yongsheng; Xu Tianqi; Vorobjeva (Vorobyeva) A. G. Anzhelika Grigorjevna; Loftenius Annika; Bodenko V. V. Vitalina Vasiljevna; Orlova A. M. Anna Markovna; Frejd Y. F. Fredrik; Tolmachev V. M. Vladimir Maksimilianovich (2023, 2023)
ABY-027 is a scaffold-protein-based cancer-targeting agent. ABY-027 includes the secondgeneration Affibody molecule ZHER2:2891, which binds to human epidermal growth factor receptor type 2 (HER2). An engineered albumin-binding domain is fused to ZHER2:2891 to reduce renal uptake and increase bioavailability. The agent can be site-specifically labeled with a beta-emitting radionuclide 177Lu using a DOTA chelator. The goals of this study were to test the hypotheses that a targeted radionuclide therapy using [177Lu]Lu-ABY-027 could extend the survival of mice with HER2-expressing human xenografts and that co-treatment with [177Lu]Lu-ABY-027 and the HER2-targeting antibody trastuzumab could enhance this effect. Balb/C nu/nu mice bearing HER2-expressing SKOV-3 xenografts were used as in vivo models. A pre-injection of trastuzumab did not reduce the uptake of [177Lu]Lu-ABY-027 in tumors. Mice were treated with [177Lu]Lu-ABY-027 or trastuzumab as monotherapies and a combination of these therapies. Mice treated with vehicle or unlabeled ABY-027 were used as controls. Targeted monotherapy using [177Lu]Lu-ABY-027 improved the survival of mice and was more efficient than trastuzumab monotherapy. A combination of therapies utilizing [177Lu]Lu-ABY-027 and trastuzumab improved the treatment outcome in comparison with monotherapies using these agents. In conclusion, [177Lu]Lu-ABY-027 alone or in combination with trastuzumab could be a new potential agent for the treatment of HER2-expressing tumors.